2007
DOI: 10.1029/2007gl029977
|View full text |Cite
|
Sign up to set email alerts
|

Tropical cyclones over the Mediterranean Sea in climate change simulations

Abstract: [1] Tropical cyclones form only under specific environmental conditions. Anthropogenic climate change might alter the geographical areas where tropical cyclones can develop. Using an ensemble of regional climate models, we find an increase in the extremes of cyclone intensity over the Mediterranean Sea under a climate change scenario. At least for the most sensitive model, the increase in intensity is clearly associated with the formation of tropical cyclones. Previous studies did not find evidence of changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 21 publications
3
54
0
1
Order By: Relevance
“…Because they are generally associated with strong winds and heavy precipitation and because their occurrence may increase under future climate change conditions (Gaertner et al, 2007), an improved knowledge of the conditions in which they develop is essential. It could lead to an improvement of their forecast and thus mitigate their potentially highly destructive effects in densely populated regions.…”
Section: Discussionmentioning
confidence: 99%
“…Because they are generally associated with strong winds and heavy precipitation and because their occurrence may increase under future climate change conditions (Gaertner et al, 2007), an improved knowledge of the conditions in which they develop is essential. It could lead to an improvement of their forecast and thus mitigate their potentially highly destructive effects in densely populated regions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the increased sea surface temperature in an anthropogenically warmed climate could lead to favorable conditions for the formation of hurricanes in the Mediterranean Sea (Gaertner et al 2007). After the advent of satellite meteorology in the last decades of the twentieth century, on the other hand, evidence emerged (Ernst and Matson 1983;Rasmussen and Zick 1987) indicating that a few mesoscale vortices showing a striking resemblance to tropical latitude hurricanes occasionally do occur over the Mediterranean Sea.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the future variations of medicane characteristics due to climate change are a matter of concern. RCMs have been used to downscale global climate model (GCM) scenarios (Gaertner et al 2007;Cavicchia et al 2014;Walsh et al 2014). Romero and Emanuel (2013) applied a statistical-deterministic method for increasing the medicane sample size.…”
Section: Introductionmentioning
confidence: 99%